Prevalence of cardiac amyloidosis in patients undergoing transcatheter edge-to edge mitral valve repair. (14th October 2021) - Dona, C; Nitsche, C; Koschutnik, M; Koschatko, S; Dannenberg, V; Kammerlander, A; Goliasch, G; Bartko, P; Schneider, M; Traub-Weidinger, T; Hacker, M; Hengstenberg, C; et al.
Abstract: Introduction: Cardiac amyloidosis (CA) is associated with severe aortic stenosis, however, its prevalence in patients with severe mitral regurgitation in elderly patients is unknown. Methods: Patients scheduled for transcatheter edge-to edge mitral valve repair (TMVR) were prospectively screened for CA using 99m technetium-3, 3-diphosphono-1, 2-propanodicarboxylic acid (DPD) bone scintigraphy and subsequent serum as well as urine free light-chain quantification in case of a positive DPD scan, defined as visual cardiac update based on the Perugini grading scale. Results: Out of 100 patients undergoing TMVR, 28 patients (28.0%) had a positive DPD-scan (DPD+). 14 patients (14.0%) showed Perugini grade I enhancement, 9 patients (9.0%) grade II enhancement, and in 5 patients (5.0%), grade III enhancement was present. 28 patients suffered from TTR and two from AL- amyloidosis (one patient had a combination of TTR and AL-amyloidosis). When compared to patients with a negative scan (DPD-), DPD+ patients presented with similar baseline characteristics such as age (DPD- vs DPD+ 76y/o vs 77y/o, p=0.44), gender (female; 62.7% vs 50.0%, p=0.25), coronary artery disease (59.7% vs 42.9%, p=0.13), previous valve surgery (25.4% vs 14.3%, p=0.24) and atrial fibrillation (68.7% vs 78.6%, p=0.33). Also, NYHA functional class and EuroScore II were similar (NYHA ≥ III; 85.1% vs 82.1%, p=0.72, and EuroScore II 9.9±9.8% vs 7.0±4.8%, p=0.21, respectively). On echocardiography, DPD+ patients presented with more pronounced left and right ventricular hypertrophy (interventricular septum: 15mm vs 13mm, p<0.01) but similar left ventricular ejection fraction (44.9% vs 42.3%, p=0.34). At 3-months after TMVR, DPD+ patients showed significant improvement in BNP serum levels when compared to DPD- patients (DPD+ vs DPD-: +315±2569pg/ml vs −2404±8696pg/ml, p=0.03), while NYHA functional class remained unchanged (NYHA improvement ≥1 class: 57.6% vs 50.0%, p=0.52) Conclusions: In this single centre experience, CA was highly prevalent among elderly patients with severe mitral regurgitation scheduled for TMVR. TMVR in CA patients resulted in significant improvement of NT-pro BNP levels. Future studies need to clarify the prognostic relevance of CA in this specific patient population. FUNDunding Acknowledgement: Type of funding sources: None.